Changes in Wood Utilization Due to Iron Age Jade Mining in the Western Hexi Corridor: Wood Charcoal Investigations - Liu, Fengwen; Yang, Yishi; Chen, Guoke; Zhang, Shanjia; Zhang, Hucai (Frontiers in Earth Science, 2021)
Charcoal remains from cultural ruins are used not only to reconstruct the historical composition of local woodlands, but also to examine the history of the use of wood by humans. Such studies have rarely addressed how and why people might have selected woody taxa from locations at long distances from their habitat. This study uses the charcoal analysis of a jade mine site in Jingbaoer, in Mazong Mountain (northwest China), to explore patterns of the collection and use of wood by humans during the Iron Age. Factors affecting the choice of wood collection at the jade mine site are discussed by combining the results of pollen records and charcoal analysis of the nearby area. The results suggest that Tamarix L., a shrub dominant in the local area, was the main source of wood for miners in Jingbaoer, and was used as firewood in proportion to its local availability. The miners might also have used wood from species located farther away, such as Pinus L. and Picea L., according to the less local availability of trees because of the dry environment. The pastoral lifestyle of the miners in Jingbaoer provide support for the hypothesis of the collection of wood from far away. This study highlights the diverse patterns of wood collection in an area scare in woody plants, and provides new evidence that can help us understand how humans in the Iron Age adapted to extreme arid environments.